Assessment of role of fetal head to perineum distance by ultrasound as a predictor of successful vaginal delivery prior to induction of labour - Singh, Richa; Yadav, Poonam; Yadav, Abhilasha; Grewal, Ishu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Objective of the study was to determine the obstetrical outcome assessed as successful vaginal delivery by using ultrasonographically measured fetal head to perineal distance. Methods: We conducted a prospective observational study on 180 antenatal women fulfilling inclusion and exclusion criteria at department of obstetrics and gynaecology, Sarojini Naidu Medical College, Agra. Trans-perineal ultrasonography for measurement of fetal head to perineum distance was done. After the scan, vaginal examination was done under all aseptic precautions to assess the various components of Bishop score (cervical position, cervical length, consistency, dilatation, station). Induction of labour was given after reaffirming that there was no contraindication for induction of labour. Monitoring of labour was done according to World Health Organization (WHO) modified partograph and cardiotocograph. Outcome of induction was considered successful if it resulted in vaginal delivery. Sensitivity and specificity of Bishop score, cervical length and foetal head to perineal distance was calculated and compared. Results: It was observed that predictability of fetal head to perineum distance measured using trans-perineal ultrasound was higher in all aspects compared to Bishop’s score and cervical length. Conclusions: The foetal head-perineum distance measured by trans-perineal ultrasound is an easy, definitive and non-invasive method for prediction of successful induction of labour and can be used as an adjunct tool to add more information to per vaginal examination findings. Based on imaging findings, patients can be counselled before induction of labour regarding the probability of successful induction.